2017
DOI: 10.1182/blood-2016-02-683169
|View full text |Cite
|
Sign up to set email alerts
|

Prophylaxis usage, bleeding rates, and joint outcomes of hemophilia, 1999 to 2010: a surveillance project

Abstract: • Bleeding in US hemophilia patients has decreased dramatically in parallel with increased use of prophylaxis.• Only prophylaxis started before age 4 years preserves normal joint function.This analysis of the US Hemophilia Treatment Center Network and the Centers for Disease Control and Prevention surveillance registry assessed trends in prophylaxis use and its impact on key indicators of arthropathy across the life-span among participants with severe hemophilia A. Data on demographics, clinical characteristic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
139
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 141 publications
(145 citation statements)
references
References 18 publications
4
139
0
2
Order By: Relevance
“…Our results regarding the increased use of prophylactic treatment and a decreased risk of bleeding concur with large-scale, prospective studies in The Netherlands [20] and the USA [22]. These studies also found reduced joint mobility in older age groups.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Our results regarding the increased use of prophylactic treatment and a decreased risk of bleeding concur with large-scale, prospective studies in The Netherlands [20] and the USA [22]. These studies also found reduced joint mobility in older age groups.…”
Section: Discussionsupporting
confidence: 89%
“…However, little change was observed in self-reported impairment of joint function among PWH > 16 years [20]. Finally, a large register-based study evaluated trends from 1999 to 2010 in bleeding rates and joint outcomes among 6,196 PWH in the USA [22]. This impressive study found increased use of prophylactic treatment and a much lower frequency of bleeding in PWH receiving prophylactic rather than on-demand treatment, but also a decline in bleeding rate over time for both groups [22].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, secondary prophylaxis (initiated post-target joint development) may not afford the same degree of benefit in terms of mobility. Consistent with this observation, a longitudinal US HTC study also showed that although prophylaxis significantly predicted decreased bleeding at any age, only prophylaxis initiation prior to age 4 (and absent obesity) predicted preservation of joint motion 32. Consistent with this observation, a longitudinal US HTC study also showed that although prophylaxis significantly predicted decreased bleeding at any age, only prophylaxis initiation prior to age 4 (and absent obesity) predicted preservation of joint motion 32.…”
supporting
confidence: 63%